The impact of brand perception resulting from the sponsorship activities of new sponsors during the 16th season of the Indian Premier League - Aparna Jha (Sampreshan, ISSN:2347-2979 UGC CARE Group 1, 2024)
In an attempt to position brands as dominant, powerful and superior to their competitors, Sports sponsorship has become a common phenomenon in today’s marketing landscape. Investors always consider sponsorship a valuable commodity because it positively impacts brand sales profitability. Given the increasing interest of numerous newer brands in sports sponsorship within the Indian Premier League (IPL). This research paper focuses on unveiling the aftermath and reverberations experienced by newly sponsored brands during the 16th season of IPL. Specifically, the impact of sponsorship activities on their brand Image has been explored, scrutinizing which sponsorship categories the audience finds more appealing. Furthermore, it also investigates the audience's perception of sponsors in the case of their favourite team underperforming. Employing a quantitative research method, data was collected through a survey questionnaire from 401 respondents aged 18-35 years old who watched the 16th IPL, primarily from Bhopal and Sagar in Madhya Pradesh. The results suggest the influence of brands sponsored for the first time in IPL on audience perceptions, attitudes and opinions.